Vera Salomons and the Kotel - reading international Jewish history through a Jewish country house - Green, A; Bergamin, P (Taylor and Francis, 2022)
Vera Bryce Salomons is best known as the founder of the L. A. Mayer Museum of Islamic Art in Jerusalem. Drawing on a privately published obituary volume, this article explores her involvement in attempts to buy Waqf property adjacent to the Kotel in the 1920s. The article brings to light a forgotten story with implications for our understanding of the role of British elites in Mandate Palestine. It demonstrates how private archives and unconventional sources can be used to illuminate the role of women in international Jewish history.